AB0197 Simvastatin Attenuates Aortic Thickness in the Chronic Reactive Oxygen Species Murine Model of Systemic Sclerosis. (10th June 2014) - Bagnato, G.; Bitto, A.; Pizzino, G.; Roberts, W.N.; Altavilla, D.; Squadrito, F.; Saitta, A.; Bagnato, G.
Abstract : Background: Systemic sclerosis (SSc) is a multisystem autoimmune disease characterized by vasculopathy and organ fibrosis. Although microvascular alterations are most prominent in SSc, a growing body of evidence exists for structural and functional abnormalities in the macrovascular circulation. Due to the predominant vascular nature of this disease, characterized by early endothelial dysfunction, there is a great need to test specific therapeutic agents. Recent evidences showed that the administration of statins in SSc patients ameliorates endothelial function and reduces the overall number of ulcers, while experimental in vivo studies suggest that statins inhibit pulmonary and cutaneous fibrosis in the reactive oxygen species murine model of systemic sclerosis 1 . Objectives: Aim of the study was therefore to evaluate the effect of simvastatin administration on aortic intima-media (IM) thickness and ratio in a murine model of systemic sclerosis. Methods: SSc–like illness was induced in BALB/c mice by daily subcutaneous injections of HOCl for 6 weeks. Mice (n=23) were randomized in three arms to treatment with either HOCl (n=10), HOCl plus simvastatin (n=8) or vehicle alone (n=5). Simvastatin treatment (40 mg/kg) was initiated 30 minutes after HOCl subcutaneous injection and continued daily for the 6 weeks. Aortic IM thickness and ratio were measured by histological methods for statistical analysis. Immunohistochemical staining for a-smooth muscle actin in aortic tissues was performed to evaluate myofibroblast differentiation. Results: In HOCl treated mice aortic IM thickness was significantly higher than controls, showing an increase of 104% (p<0.0001). Administration of simvastatin diminished this increase by 92% (p<0.0001). IM ratio was also decreased in HOCl treated mice compared to controls (0.75 vs 1.75, p<0.0001) and significantly increased by simvastatin administration (1.61 vs 0.75, p<0.0001). Myofibroblast differentiation, as determined by a-SMA staining in aortic tissues, was attenuated in mice treated by HOCl + simvastatin compared to mice treated with HOCl (p<0.0001) Conclusions: Although in the last decades SSc death rates due the atherosclerotic cardiovascular diseases or cerebrovascular diseases increased 2, remains controversial whether there is accelerated atherosclerosis in systemic sclerosis 3 . Administration of simvastatin moderates the increase of IM thickness in the reactive oxygen species murine model of SSc and reduces the number of αSMA+ cells. Further studies are needed to better address the effect of statins in the macrovascular component of SSc. References: Bagnato G., Bitto A., Pizzino G, Irrera N, Sangari D, Cinquegrani M, Roberts WN, Matucci Cerinic M, Squadrito F, Altavilla D, Bagnato G, Saitta A. Simvastatin attenuates the development of pulmonary and cutaneous fibrosis in a murine model of systemic sclerosis. Rheumatology (Oxford). 2013 Aug;52(8):1377-86. Belch JJ, McSwiggan S, Lau C. Macrovascular disease in systemic sclerosis: the tip of an iceberg? Rheumatology (Oxford) 2008;47(Suppl 5):v16–7 Nussinovitch U, Shoenfeld Y. Atherosclerosis and macrovascular involvement in systemic sclerosis: myth or reality. Autoimmun Rev. 2011 Mar;10(5):259-66 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2465